Памятники у с. Беспальче Драбовского р-на Черкасской обл. - Лысенко, С.Д.; Куштан, Д.П.; Дяченко, А.В.; Разумов, С.Н.; Федько, В.Ф. (Археологічні дослідження в Україні, 2010)
Materials from settlements of various periods discovered near Bespalche village of Drabiv Region in Cherkasy Oblast are presented. The finds of Trypillya culture and the Bronze Age are described in detail.